Circadian control of innate immunity in macrophages by miR-155 targeting Bmal1. - CURTIS, ANNIE; O'NEILL, LUKE; HOKAMP, KARSTEN (My University, 2015)
The circadian clock allows an organism to anticipate daily changes imposed by the environment. The response to LPS is altered depending on time of day; however, the molecular mechanisms underlying this are unclear. We find that the clock in myeloid cells plays a role in LPS-induced sepsis by altering NF-κB activity and the induction of the microRNA miR-155. LPS causes the repression of BMAL1 via the targeting of miR-155 to two seed sequences in the 3′-untranslated region of Bmal1. Lack of miR-155 has profound effects on circadian function and circadian induction of cytokines by LPS. Thus, the molecular clock is using miR-155 as an important regulatory component to control inflammation variably across the circadian day in myeloid cells
PUBLISHED
Keywords: inflammation, sepsis, circadian clock, miR-155, Bmal1; inflammation, sepsis, circadian clock, miR-155, Bmal1; Immunology, Inflammation & Infection; Toll-Like Receptors